Earl Swagger: The Bullet Garden - Book 4 - Hunter, Stephen, 1946- (Thorndike, Maine : Center Point Large Print, 2023)
"July, 1944: The lush, rolling hills of Normandy are dotted with a new feature - German snipers. From their vantage points, they pick off hundreds of Allied soldiers every day, bringing the D-Day invasion to its knees. Its clear that someone is tipping off these snipers with the locations of American GIs, but who? And how? General Eisenhower demands his intelligence service to find the best shot in the Allied military to counter this deadly SS operation. Enter Pacific hero Earl Swagger, assigned this crucial and bloody mission. With crosshairs on his back, Swagger cant trust anyone as he infiltrates the shadowy corners of London and France for answers."--
Keywords: Swagger, Earl (Fictitious character) -- Fiction; Snipers -- Fiction; World War, 1939-1945 -- Campaigns -- France; Normandy; Fiction; Espionage -- Fiction; Spy fiction; Thrillers (Fiction); War fiction; Historical fiction; Large print books